The establishment of the Ottoman State in the Balkans - Zens, Robert (My University, 1998)
Contents include: the birth of a dynasty, the internal collapse of the Byzantine Empire, the rise and fall of Serbia and Bulgaria, Byzantium looks westward for help, Ottoman unity and the successes of Murad, the Ottoman system of rule in the Balkans, Sultan Bayezid's conquests, Bayezid's Anatolia campaign, the Ottoman Civil War 1403-13, and reunited Ottoman state under Sultan Mehmet.
iii, 93 leaves ; 29 cm.